Reactive oxygen species may be involved in the distinctive biological effects of different doses of 12C6+ ion beams on Arabidopsis - Yin, Yue; Cui, Dongjie; Chi, Qing; Xu, Hangbo; Guan, Panfeng; Zhang, Hanfeng; Jiao, Tao; Wang, Xiaojie; Wang, Lin; Sun, Hao (Frontiers in Plant Science, 2024)
Introduction Heavy ion beam is a novel approach for crop mutagenesis with the advantage of high energy transfer line density and low repair effect after injury, however, little investigation on the biological effect on plant was performed. 50 Gy irradiation significantly stimulated the growth of Arabidopsis seedlings, as indicated by an increase in root and biomass, while 200 Gy irradiation significantly inhibited the growth of seedlings, causing a visible decrease in plant growth. Methods The Arabidopsis seeds were irradiated by 12C6+. Monte Carlo simulations were used to calculate the damage to seeds and particle trajectories by ion implantation. The seed epidermis received SEM detection and changes in its organic composition were detected using FTIR. Evidence of ROS and antioxidant systems were analyzed. RNA-seq and qPCR were used to detect changes in seedling transcript levels. Results and discussion Monte Carlo simulations revealed that high-dose irradiation causes various damage. Evidence of ROS and antioxidant systems implies that the emergence of phenotypes in plant cells may be associated with oxidative stress. Transcriptomic analysis of the seedlings demonstrated that 170 DEGs were present in the 50 Gy and 200 Gy groups and GO enrichment indicated that they were mainly associated with stress resistance and cell wall homeostasis. Further GO enrichment of DEGs unique to 50 Gy and 200 Gy revealed 58 50Gy-exclusive DEGs were enriched in response to oxidative stress and jasmonic acid entries, while 435 200 Gy-exclusive DEGs were enriched in relation to oxidative stress, organic cyclic compounds, and salicylic acid. This investigation advances our insight into the biological effects of heavy ion irradiation and the underlying mechanisms.